Challenges of HIV and AIDS Implementation Policy in Primary Schools in Mbale District in Uganda - Gidudu , Hannah Lunyolo (African Journal of Education,Science and Technology (AJEST), 2014)
HIV and AIDS Workplace policies are designed guidelines for employee behavior, criteria for performance evaluations and ways to make the workplace more productive.This research sought to establish the management responses in addressing the challenges of implementing the HIV/AIDS policy in primary schools in Mbale district.The researcher used stratified sampling techniques to select headteachers, teachers and education officials.The study was carried out in five primary schools of which two were privately owned and three governments -aided. From each of these schools, a head teacher and ten teachers were selected to participate in the study. Data was also obtained from three district officials, namely; the Education Officer, the Inspector of schools and the district HIV/AIDS focal person. The Researcher used a mixed method research design to collect, and analyze the data. The study revealed that there are measures in place to address the challenges of HIV/AIDS policy implementation though they are not effective. These measures are at two levels, thus, district and at school level. At district level, HIV/AIDS has been mainstreamed, establishment of partnership with NGOs to facilitate access to youth friendly services for prevention, care and support, there is good collaboration with non- government organizations and agencies in conducting HIV/AIDS activities, putting in place the HIV/AIDS Focal Point Person and establishment of HIV/AIDS structures. At school level; HIV/AIDS is main-streamed in school development plans, and counselling rooms have been put up in some schools, equipping of pupils with basic knowledge on HIV/AIDS, carrying out regular sensitization, training teachers on HV/AIDS counselling skills, and formation of Ant-AIDS clubs. From the study findings, the district should strengthen the HIV/AIDS structures for easy implementation process and Counselling rooms should be constructed, in all schools